LINC00460 Promotes Cell Proliferation, Migration, Invasion, and Epithelial-Mesenchymal Transition of Head and Neck Squamous Cell Carcinoma via miR-320a/BGN Axis - Yang, Yifan (Onco Targets Ther, 2021)
PURPOSE: Long non-coding RNAs (lncRNAs) play critical roles in cancer onset and development, including head and neck squamous cell carcinoma (HNSCC). This study aimed to investigate the biological role of LINC00460 and the mechanisms underlying epithelial-mesenchymal transition (EMT) in HNSCC. METHODS: Aberrantly LINC00460 expression in HNSCC and overall survival outcomes were constructed using the TCGA database. Quantitative real-time polymerase chain reaction (RT-qPCR) was applied to examine the LINC00460 expression level in HNSCC cell lines. The role of LINC00460 knockdown on HNSCC cell growth, migration, invasion, and EMT was investigated in vitro using cell counting kit-8 (CCK-8), colony formation, transwell assay, and Western blot assay. Besides, bioinformatics prediction, dual-luciferase reporter assay, and RNA immunoprecipitation (RIP) were performed to reveal the interaction among LINC00460 and its target genes. The function of the LINC00460/miR-320a/BGN axis in HNSCC cells was clarified by rescue assays. Furthermore, the in vivo effects of LINC00460 on tumor growth were investigated using mice xenograft models. RESULTS: In this study, LINC00460 was upregulated in HNSCC tissues and cells and was associated with poor clinical prognosis. Further functional analysis showed that LINC00460 knockdown decreased HNSCC cell proliferation, migration, invasion, as well as EMT in vitro. Mechanistic investigation indicated that LINC00460 sponged miR-320a to upregulate Biglycan (BGN) expression, thereby facilitating HNSCC progression and induced EMT. Moreover, knockdown of LINC00460 significantly suppressed the progression of HNSCC cells in vivo. CONCLUSION: Taken together, LINC00460 mediates miR-320a/BGN signaling axis to promote cell proliferation, migration, invasion, and induce the EMT process in HNSCC cells. Our findings elucidated a novel mechanism underlying the progression of HNSCC. LINC00460 could serve as a potential therapeutic target for the treatment of HNSCC.